ياءات الإضافة في رواية حفص: دراسة صوتية مقطعية - شوك، محمد عادل بن أحمد (جامعة أسيوط - كلية الآداب, 2022)
هذا بحث صوتي في أصل من أصول رواية حفص عن عاصم، نظر فيه الباحث في مسألة (الإسكان، والإرسال: الفتح)، في باب (ياءات الإضافة). لقد شدني للحديث عنه ما رأيته من الاقتصار عند القدماء، في جعل الحديث عنه لا يعدو كون (الإسكان، والإرسال) لغة من لغات العرب، أو أنه من باب (الأصل والفرع). استندت فيه إلى ما استجد في الدراسات الصوتية، ولما راج لدى المحدثين في قضية المقاطع الصوتية، التي أصبح الحديث فيها من السمات التي تتمايز وفقها اللغات عن بعضها البعض، وذلك أن لكل لغة مقاطعها التي ينتظم في عقد كلماتها وألفاظها. اعتمدت فيه المنهج الوصفي التحليلي، الذي سينقل القراءة من مظانها المتقدمة، ثم يصفها بوسائل التعليل والتحليلي والتفسير من خلال كتب النحو واللغة والتفسير والمعاني وعلل القراءات، مفيدًا من معطيات الدرس الحديث، حينما يضفي ذلك على الظاهرة تعليلًا أو تفسيرًا جديدًا يضاف إلى تعليلات المتقدمين، وذلك باستخدام المقاطع الصوتية، التي ساعدت الباحثين كثيرًا في تحليل الظواهر الصوتية والصرفية. This is an audio research on one of the origins of the narration of Hafs on the authority of Asim, examining the issue of Iskan and Issal (Al-Fath) in the chapter (Ya’at al-Adhadah). It was based on what has been updated in phonetic studies, and what was modern scholars regarding the issue of phonemic syllables, in which hadith has become one of the features according to which languages are distinguished from each other, because every language has its syllables that are organized in the contract of its words and expressions. The descriptive-analytical approach was adopted, which will transfer the reading from its advanced perspectives, and then describe it by means of reasoning, analysis and interpretation through books of grammar, language, interpretation, meanings and the ills of the readings, useful from the data of the modern lesson, when it gives the phenomenon a new explanation or interpretation added to the explanations of the applicants, and that Using audio clips, it has helped researchers a lot in analyzing phonemic and morphological phenomena.
Keywords: القراءات القرآنية -- القرآن الكريم -- رواية حفص -- ياء الإضافة -- علم القراءات